2017
DOI: 10.1155/2017/9538351
|View full text |Cite
|
Sign up to set email alerts
|

Hydroethanolic Extract of Strychnos pseudoquina Accelerates Skin Wound Healing by Modulating the Oxidative Status and Microstructural Reorganization of Scar Tissue in Experimental Type I Diabetes

Abstract: The effect of topical application of ointment based on Strychnos pseudoquina hydroethanolic extract in the cutaneous wounds healing in diabetic rats was evaluated. Samples of S. pseudoquina were submitted to phytochemical prospection and in vitro antioxidant assay. Thirty Wistar rats were divided into 5 groups: Sal-wounds treated with 0.9% saline solution; VH-wounds treated with 0.6 g of lanolin cream (vehicle); SS-wounds treated with silver sulfadiazine cream (10 mg/g); ES5- and ES10-wounds treated with an oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 75 publications
(104 reference statements)
1
11
0
2
Order By: Relevance
“…Higher blood AST and ALT found in our study also seems to support a hypothesis of an overall malfunction of the body caused by excessive free-radical generation, delaying the healing process [ 43 , 46 ]. The newly formed granulation tissue, along with cells and blood vessels, presents fibrillary components that support cell migration and act as a scaffold for tissue maturation, providing the new skin with resistance and strength [ 46 48 ]. Our results showed that the administration of a combined high-fat diet and alcohol delayed type I and type III collagen deposition, impairing cell migration and fiber synthesis and remodeling.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Higher blood AST and ALT found in our study also seems to support a hypothesis of an overall malfunction of the body caused by excessive free-radical generation, delaying the healing process [ 43 , 46 ]. The newly formed granulation tissue, along with cells and blood vessels, presents fibrillary components that support cell migration and act as a scaffold for tissue maturation, providing the new skin with resistance and strength [ 46 48 ]. Our results showed that the administration of a combined high-fat diet and alcohol delayed type I and type III collagen deposition, impairing cell migration and fiber synthesis and remodeling.…”
Section: Discussionsupporting
confidence: 87%
“…Increases in these two oxidative stress markers indicate possible membrane and protein cell lesions, possibly due to a continuous effect of a stressor. These indicative alterations may include an initial inflammation with reversible lesions and later necrosis or apoptosis [ 15 , 46 , 60 ]. Acetaldehyde oxidation and pH alterations to the epidermis stratum corneum were also reported as factors extending the inflammation process in scar tissue when ethanol consumption is involved [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of other phytochemicals are reported in literature with potential effects on skin, such as anti-age activity [169], photoprotection [170], wound healing [171], and anti-infection [172].…”
Section: Phytochemicals In Skin Diseasesmentioning
confidence: 99%
“…These compounds have therapeutic effects against diabetic complications such as diabetic retinopathy 10 . Specifically, several studies have reported that chlorogenic acid has a protective effect on skin wound healing in DM 12, 18, 19. To our knowledge, no study has reported the effects of 3,5-di-O-caffeoylquinic acid on diabetic wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that the AKE improved diabetic complications such as diabetic retinopathy 10 . Several studies have reported that skin wound healing is impaired and delayed in hyperglycemia 4, 5, 12. However, the effect of AKE on hyperglycemia-induced impaired wound healing has not been investigated and the mechanisms underlying these effects remain unknown.…”
Section: Introductionmentioning
confidence: 95%